Marxist history and historians in the 20th Century. - Torr, Dona; Archive Trust of the Communist Party of Great Britain (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2021)
Dona Ruth Anne Torr (1883-1957) was a Marxist historian, translator and activist. Despite being born into an aristocratic family, Torr became a founding member of the Communist Party of Great Britain (CPGB). She went on to build a reputation not only as an adept historian, but also as a passionate activist who gave her life to communism. She has been cited as a major influence by E.P. Thompson and Eric Hobsbawm. This collection contains Torr’s personal papers, including research notes and other materials relating to her biography of noted labour activist Thomas Mann. Together, these documents provide an invaluable insight into Marxist historiography and the social history of the British labour movement. In addition, they shed light on the life and times of one of British communism’s most important female figures.
Date range: 1900-1999.
Keywords: Torr, Dona -- Correspondence; Torr, Dona -- Notebooks, sketchbooks, etc; Communism -- Great Britain -- History -- 20th century -- Sources